A descriptive analysis of the warm-up strategies of cross-country skiers - Jones, T.; Govus, A.; Buskqvist, A.; Andersson, E. (Nordic Winter Sport Conference, 2020)
In: A descriptive analysis of the warm-up strategies of cross-country skiers, 2020 Conference paper, Poster (with or without abstract) (Refereed) Abstract [en] Purpose: To provide a descriptive account of the warm up strategies (WU) employed by cross country skiers prior to distance and sprint competitions at a national championship; analyze the skiers` planned WU; compare skiers` planned and actual WUs carried out prior to the respective competitions.